2022
DOI: 10.1186/s12951-022-01350-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of G2-S16 dendrimer as microbicide in healthy human vaginal tissue explants

Abstract: Background The absence of an effective treatment and vaccine in HIV-1 pandemic place preventive strategies such as safety and effective microbicide development as a central therapeutic approach to control HIV-1 pandemic nowadays. Results Studies of cytotoxicity, immune population status, inflammation or tissue damage and mainly prophylactic inhibition of HIV-1 infection in vaginal human explants demonstrate the biosafety and effectivity of G2-S16 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The limitations of traditional antiviral therapies against HCMV infection have led to the development of novel treatments, including genetic, cellular and immune therapies [20]. Among these alternatives, dendrimers have demonstrated efficacy against different pathogens, including HCMV [21][22][23]. Our study highlights the combined immune effect of PCDs G2-S16 and G2-S24P with the immunomodulatory capacity of Tα1, showing their ability to enhance the functionality of DCs as antigen-presenting cells (APCs) and subsequently boost the activation of T cells, including Treg, promoting an adaptive response against HCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of traditional antiviral therapies against HCMV infection have led to the development of novel treatments, including genetic, cellular and immune therapies [20]. Among these alternatives, dendrimers have demonstrated efficacy against different pathogens, including HCMV [21][22][23]. Our study highlights the combined immune effect of PCDs G2-S16 and G2-S24P with the immunomodulatory capacity of Tα1, showing their ability to enhance the functionality of DCs as antigen-presenting cells (APCs) and subsequently boost the activation of T cells, including Treg, promoting an adaptive response against HCMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Summary of main in vivo assays performed with polyanionic carbosilane dendrimer G2‐S16 as vaginal microbicides against HSV. Reprinted with permission from Rodríguez‐Izquierdo, Serramía, et al (2022). Copyright© 2022, Wiley…”
Section: Pharmaceutical Applications Of Carbosilane Dendritic Moleculesmentioning
confidence: 99%
“…[ 82 ] AuNPs have the capacity to cross de blood–brain barrier in mice model, without cerebral damage, and inhibiting HSV‐1 infection. [ 83 ] Interestingly, the authors reported that AuNPs also reduced HSV‐1 induced β‐secretase activity, which is related to Alzheimer's disease. [ 84 ] Copper nanoparticles (CuNPs) at 100 µg mL −1 significantly decreased virus titers (HSV‐1) with an inhibition rate of 83.3%.…”
Section: Human Viral Diseases and Nanoparticlesmentioning
confidence: 99%